Control of diffusion-driven pattern formation behind a wave of competency - Liu, Y; Maini, P; Baker, R (Elsevier, 2022)
In certain biological contexts, such as the plumage patterns of birds and stripes on certain species of fishes, pattern formation takes place behind a so-called “wave of competency”. Currently, the effects of a wave of competency on the patterning outcome are not well-understood. In this study, we use Turing’s diffusion-driven instability model to study pattern formation behind a wave of competency, under a range of wave speeds. Numerical simulations show that in one spatial dimension a slower wave speed drives a sequence of peak splittings in the pattern, whereas a higher wave speed leads to peak insertions. In two spatial dimensions, we observe stripes that are either perpendicular or parallel to the moving boundary under slow or fast wave speeds, respectively. We argue that there is a correspondence between the one- and two-dimensional phenomena, and hypothesize that (as others have) pattern formation behind a wave of competency can account for the pattern organization observed in many biological systems.